THE I3A FRAMEWORK – ENHANCING OFF-GRID PHOTOVOLTAIC ENERGY SERVICE DELIVERY IN INDONESIA - Retnanestri, M; Outhred, H.; Healy, S. (Agency for the Assessment and Application of Technology)
This paper describes an interdisciplinary research project to investigate the sustainability of off-grid Photovoltaic Energy Service (PVES) delivery in Indonesia. The paper describes results from the preliminary fieldwork undertaken in late 2002 and early 2003, more substantive fieldwork was carried out in 2005. The general objective of this research project is to understand how PVES can contribute to improving the life of rural Indonesian communities having no access to the electricity grid. It adopts an interdisciplinary approach that combines social and engineering perspectives to address sustainability issues. The I3A (Implementation, Accessibility, Availability, Acceptability) Sustainable PVES Delivery framework was developed to assess sustainability and was used to assess three off-grid PVES case studies in Lampung, West Java and Nusa Tenggara Timur (NTT) provinces. The overall objectives of the I3A framework are to acknowledge the interests of stakeholders, maximize equity, assure PVES continuity and institutionalize PVES by utilizing and enhancing pre-existing community resources to leave host communities with the capacity to meet evolving needs. A key conclusion is that, to be sustainable and equitable, off-grid PVES projects should be implemented in an institutional framework that provides sound project management and addresses PVES accessibility (financial, institutional and technological), availability (technical quality and continuity) and acceptability (social and ecological).